Psychosocial Risk Factors at Group Level and Operational Distress among Employees in Salvadoran Companies (London Journal of Research In Humanities and Social Sciences, 2024)
The study of psychosocial risks at the group level and operational distress among employees in Salvadoran companies is scarcely addressed, despite the significant importance organizations place on this issue. This study aims to understand employees' perceptions of these psychosocial risks and distresses through an assessment of their prevalence using the Healthy Talent Model and HTMetrics PCAS Tool, with the goal of proposing interventions to mitigate negative impacts. A descriptive analysis using frequency tables was conducted. The findings confirm the prevalence of occupational stress, the presence of psychosocial risks at the group level, and operational distress. Finally, various levels of intervention are proposed to address these issues in Salvadoran companies.
Keywords: morality.; will; greed; Dependence; freedom; necessity; fate; fatalism; moral goodnefreedom; moral goodness; choice.ss; choice.; Psychosocial Risks; Operational Distress; Employees; Public and Private Organisations